Sharia Banking Perspectives on Inflation And Economic Stability: Qualitative Insights And Policy Implications - Feri Hardiyanto; Agus Rohmat Hidayat; Rudi Ferdiansah (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Inflation and economic instability remain major concerns in developing economies, including Indonesia. Inflation reduces purchasing power, increases production costs, affects household welfare, and creates uncertainty for financial institutions.. Indonesia’s Islamic banking sector has grown significantly, with assets exceeding IDR 800 trillion and a market share of approximately 7.5% of total national banking assets as of 2023, underscoring its increasing relevance as a stabilizing financial force in an inflation-prone economy.Objective: This study aims to examine inflation and economic stability from the perspective of sharia banking and to identify relevant policy implications for strengthening financial resilience in Indonesia.Methods: This study uses a qualitative literature review approach by synthesizing previous studies related to inflation, Islamic finance, monetary policy, sharia banking, digital finance, MSMEs, and macroeconomic uncertainty.Results: The findings show that inflation weakens purchasing power, increases business uncertainty, and affects financial performance. Sharia banking can contribute to economic stability through third-party fund mobilization, productive financing, ethical financial governance, and support for MSMEs. Eight thematic clusters were identified: inflation and welfare, banking performance risk, sharia banking and economic growth, MSME resilience, exchange rate dynamics, monetary policy coordination, digital financial transformation, and the Islamic finance ecosystem.Conclusion: Sharia banking can serve as a complementary pillar in Indonesia’s economic stability framework. Policy integration between monetary authorities, Islamic financial institutions, and real-sector development is needed to reduce inflationary pressure and strengthen inclusive economic resilience. This study contributes an integrative policy-relevant framework positioning sharia banking as an institutional actor in inflation mitigation and inclusive financial development in Indonesia.